Denosumab and Bisphosphonate Treatment of Osteoporosis in Renal Transplant Recipients - Şahin, Serdar; Dinçer, Mevlüt Tamer; Seyhan, Duygu; Bakır, Alev; Polat Korkmaz, Özge; Durcan, Emre; Mefkure Özkaya, Hande; Trabulus, Sinan; Seyahi, Nurhan; Gönen, Mustafa Sait (Cerrahpaşa Medical Journal, 2021)
Objective: Kidney transplant recipients are at risk of losing bone mineral density. Osteoporosis and fractures cause serious complications in renal transplant recipients. We aimed to evaluate the efficacy and safety of bisphosphonate and denosumab treatments. Methods: Thirty-two renal transplant patients with osteoporosis from Division of Nephrology of İstanbul University-Cerrahpaşa were retrospectively evaluated. Ten patients were treated with denosumab, 22 patients were treated with bisphosphonate. Time elapsed after transplantation, cumulative steroid doses, baseline and first-year calcium, phosphorus, parathyroid hormone, and the glomerular filtration rate were compared. The initial and first-year femur and lumbar bone mineral densities were compared for both groups separately. Results: The baseline femur bone mineral density was significantly lower in the denosumab arm, but there was no significant difference between the initial lumbar bone mineral densities between groups. There was a significant increase in lumbar bone mineral density for both the denosumab and bisphosphonate arms in the first year of treatment. For both groups, there was no significant increase in femur bone mineral density in the first year of treatment. The time elapsed after transplantation and cumulative steroid dose were higher in the denosumab arm. Glomerular filtration rate levels of the denosumab arm were lower compared to bisphosphonate arm. Hypocalcemia associated with antiresorptive agent was not found in the treatment arms. In the first year of treatment, calcium levels were significantly lower in the denosumab treatment arm. Conclusion: Denosumab is an effective treatment option, especially in renal transplant patients with a low glomerular filtration rate. Cite this article as: Şahin S, Dinçer MT, Seyhan D, et al. Denosumab and bisphosphonate treatment of osteoporosis in renal transplant recipients. Cerrahpaşa Med J. 2021;45(3):152-158.